Metode Perubahan Undang-Undang Dasar 1945 dan Perbandingannya dengan Konstitusi di Beberapa Negara - Taufiqurrohman Syahuri (Jurnal Hukum IUS QUIA IUSTUM, 2010)
The process of amending UUD 1945 has created different kinds of views regarding its form of amendment. One side demands “amendment system” as the one applied in United State of America. The other side demands a total change by creating a new constitution such as in France, Netherlands, and Germany. The main problem that would be investigated and answered in this research is how the amendment of constitution in theory and constitutions in several countries. This research is a case study about the method used in the amendment of constitution. The approach used in this research is not only normative jurisdiction, but also comparative approach, because it has normative comparison on the constitutions in several countries. This research has concluded; first, the way UUD 1945 amended theoretically does not divert from the general principles of constitution changing and democracy country. Second, the amendment of UUD 1945 follows the form of the amendment or constitutional adandum of United States of America.Key words : Constitution, amendment, UUD 1945